Splenectomy and chronic thromboembolic pulmonary hypertension. Issue 12 (5th August 2005) - Jaïs, X; Ioos, V; Jardim, C; Sitbon, O; Parent, F; Hamid, A; Fadel, E; Dartevelle, P; Simonneau, G; Humbert, M
Abstract : Background: An increased prevalence of splenectomy has been reported in patients with idiopathic pulmonary arterial hypertension. Examination of small pulmonary arteries from these subjects has revealed multiple thrombotic lesions, suggesting that thrombosis may contribute to this condition. Based on these findings, we hypothesised that splenectomy could be a risk factor for chronic thromboembolic pulmonary hypertension (CTEPH), a condition defined by the absence of thrombus resolution after acute pulmonary embolism that causes sustained obstruction of the pulmonary arteries and subsequent pulmonary hypertension. Methods: The medical history, clinical characteristics, thrombotic risk factors and haemodynamics of 257 patients referred for CTEPH between 1989 and 1999 were reviewed. In a case-control study the prevalence of splenectomy in patients with CTEPH was compared with that of patients evaluated during the same period for idiopathic pulmonary hypertension (n = 276) or for lung transplantation in other chronic pulmonary conditions (n = 180). Results: In patients with CTEPH, 8.6% (95% CI 5.2 to 12.0) had a history of splenectomy compared with 2.5% (95% CI 0.7 to 4.4) and 0.56% (95% CI 0 to 1.6) in cases of idiopathic pulmonary arterial hypertension and other chronic pulmonary conditions, respectively (p<0.01). Conclusion: Splenectomy may be a risk factor for chronic thromboembolic pulmonary hypertension.